Estudo dopplerfluxométrico renal de quatis (Nasua nasua, Linnaeus, 1766) de vida livre - Inamassu, Letícia Rocha [UNESP] (2015)
Coati's population has increased considerably, especially in public parks, which increases the concern about the occurrence of zoonotic diseases. There are few reports of the use of conventional and Doppler ultrasound in renal evaluation of these animals, as well as an aid in the disease diagnosis in this species. Therefore, the study aimed to assess by conventional ultrasound the characteristics of comparative echogenicity of the kidneys and to detect at Doppler examination, a profile of the resistivity index of intrarenal arteries of free ranging coatis under chemical restraint. Seventeen coatis, 4 males and 13 females, were evaluated. A positive correlation was observed between body weight (from 2.5 to 9.3 kg) and renal length (from 2.73 to 4.07cm). All coatis had adequate cortico-medullary definition and ratio, with a hyperechoic cortex relative to the medulla, maintaining the same echogenicity relationship between splenic and hepatic parenchyma and renal cortex than those observed in dogs and cats. The resistive index (RI) was obtained from the intrarenal arteries, averaging 0.62 ± 0.06 (range 0.49 to 0.71) and mean systemic arterial pressure (SAP) of 95.06 mmHg, a higher RI than those found in dogs and cats not sedated. There was no positive correlation between SAP and renal RI in the animals submitted to a combination of ketamine, xylazine and midazolam. The RI of these animals should be measured with other chemical combinations of anesthetics